(untitled) (Majalah Kedokteran Bandung, 2020)
The incidence of obesity in Indonesia has increased from 14.8% in 2013 to approximately 21.8% in 2018. There is no published data regarding assessments on functional outcomes and complication after Anterior Cruciate Ligament (ACL) reconstruction in patients with different Body Mass Index (BMI) in Indonesia. The aim of this study was to describe the distribution of ACL injury and compare the functional outcomes after ACL reconstruction using hamstring tendon autograft in patients with different BMI categories.This was a retrospective study in 2 groups of patients with different BMI categories: normal BMI group (18.5 to 24.99) and high BMI group (â‰¥25), who had undergone surgeries for ACL injury in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, during the period of 2017 to 2018. Data were collected from medical records and direct examination on functional outcome measurement using Lysholm score.This study comprised of 71 patients who were followed for a minimum of 6 months. Of 71 patients, 43 were in the normal BMI group and 28 were in the high BMI group. No significant differences in postoperative functional outcome between the groups when assessed using Lysholm score. In normal BMI group 95% were graded as excellent to good while5% were in the fair functional category. Meanwhile, in the high BMI group, 86% were graded as excellent to good and 14% were graded as having fair functional results. ACL reconstruction with Hamstring tendon autograft results in a good functional score and a high succes rate in both BMI groups. High BMI does not adversely affect functional outcomes as both BMI groups gain equal benefits. Rekonstruksi Anterior Cruciate Ligament Menggunakan Autograft Tendon Hamstring Insidensi obesitas di Indonesia meningkat dari 14.8% pada tahun 2013 menjadi 21.8% pada tahun 2018. Tidak ada publikasi data yang menilai hasil akhir fungsional dan komplikasi setelah operasi rekonstruksi Anterior Cruciate Ligament (ACL) pada pasien dengan indeks massa tubuh (IMT) yang berbeda di Indonesia. Tujuan dari penelitian ini membandingkan hasil akhir fungsional menggunakan skor Lysholm setelah rekonstruksi ACL pada pasien dengan IMT yang berbeda. Penelitian ini bersifat retrospektif yang dibagi menjadi 2 kelompok penelitian dengan IMT yang berbeda; yaitu IMT normal (18.5–24.99) dan IMT yang tinggi (â‰¥25), yang dilakukan operasi cedera ACL di Rumah Sakit Hasan Sadikin periode tahun 2017-2018. Penelitian ini terdiri dari 71 pasien dan dilakukan pengamatan selama minimal 6 bulan dengan jumlah pasien kelompok IMT normal sebesar 43 pasien, sedangkan 28 pasien pada kelompok IMT yang tinggi. Tidak ada perbedaan signifikan diantara kedua kelompok pada hasil akhir fungsional pasca operasi ACL. Kelompok IMT normal terdiri dari 95% dinilai sebagai excellent sampai good dan 5% dinilai sebagai fair, sedangkan untuk kelompok IMT yang tinggi terdiri dari 86% dinilai sebagai excellent sampai good dan 14% dinilai sebagai fair hasil fungsional. Simpulan, operasi rekonstruksi ACL memiliki skor akhir fungsional yang bagus dan angka kesuksesan yang tinggi pada kedua kelompok IMT.